Synthesis and Characterization of mpeg-PCL Copolymers as a Polymersomes for Delivery of Enalapril as a Model Hydrophilic Drug: Drug delivery of enalapril by polymersomes - Danafar, Hossein (Iranian Journal of Pharmaceutical Sciences, 2018)
Enalapril maleate (EPM) was used for hypertension and congestive heart failure. In this way, an innovative delivery system with mPEG–PCL was synthesized and the release profile of the EPM from the drug-loaded polymersomes was evaluated. Di-block methoxy-poly (ethylene glycol) - poly (caprolactone) (mPEG-PCL) copolymers were synthesized and used to prepare polymersomes for the controlled release of EPM as hydrophilic model drug. mPEG-PCL copolymer was characterized in vitro by HNMR, FTIR, DSC, and GPC techniques. The resulting polymersomes were characterized further by various techniques such as dynamic light scattering (DLS) and transmission electron microscopy (TEM). The results of TEM show the polymersomes formed had spherical structure and the size of polymersomes is 80 nm. The loading and encapsulation efficiency of EPM were determinate by HPLC at 215 nm with loading and encapsulation efficiency 19.8% ± 2.12% and 85.6% ± 1.26%, respectively. In vitro release of EPM from polymersomes was clearly sustained in all the time tested for this purpose. The sustained release of drug was hypothetically due to the entrapment of EPM in core of polymersomes. The results indicate the successful formulation of EPM loaded m-PEG/PCL polymersomes. Overall, the results demonstrated that m-PEG-PCL polymersomes can be considered as a promising carrier for hydrophilic drugs such as EPM.